The effectiveness of technologies for accessing information for people with disabilities in Saudi society: A case study of the Eastern Province (Dammam) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to evaluate the effectiveness of assistive technologies in enabling people with disabilities to access information in Saudi society. It relied on a case study approach and an electronic questionnaire administered to a random sample of people with disabilities in Dammam, Eastern Province. The questionnaire included three main themes, and 85 individuals with various disabilities participated. The results showed that 94.1% of participants (80 individuals) use assistive technologies to access information, while only 5.9% (5 individuals) do not use them. This reflects the growing role of technology in facilitating various aspects of life such as communication, education, shopping, and work. Among technology users, sound enhancement headphones for hearing impairments ranked first at 37.5% (30 individuals), followed by smart applications for mental disabilities at 21.1% (17 individuals). 67% of participants (57 individuals) confirmed that they do not face difficulties when using technology, which indicates the effectiveness of these tools for a good percentage of users. The recommendations include: Enhancing the technical infrastructure by providing various assistive technologies that take into account the different types of disabilities (motor, visual, hearing, mental) to be more inclusive, designing comprehensive technical solutions that support all types of disabilities, with a focus on mental disabilities that suffer from a lack of appropriate tools, considering the design of digital interfaces that take into account individual differences in sensory and motor abilities, and providing specialized training and rehabilitation for people with disabilities to use modern technologies. Integrating interactive learning tools such as smart boards and eye-tracking devices into classrooms.
Keywords: Effectiveness; Information Technology; Access to Information; People with Disabilities; Saudi Society